Digital Transformation of Smart Parking: A Design Science Research Study - Eliyah Acantha Manapa Sampetoding; Andi Ahmad Fa’il Fudhayl; Kelvin Leonardo Sianipar; Mario Valerian Rante Ta’dung (Journal of Information System Research (JOSH), 2026)
This research discusses the design and development of a digital transformation concept for a parking system in the context of smart city development in Makassar, Indonesia. This research was conducted in response to the problems of illegal parking and low accountability for parking revenues, which impact regional income and the quality of parking services. This research resulted in an information system in the form of an artifact model, developed using a Design Science Research (DSR) approach, including the stages of design, model building, demonstration, and conceptual evaluation of the artifact. The resulting model has not been implemented as an operational mobile application, but rather compiled as a conceptual and technical design that is validated through presentations and discussions with relevant stakeholders and potential users (the public) as part of the demonstration phase within the DSR framework. The research methods include needs analysis, system design, technology selection, system architecture design, and conceptual evaluation based on the Hevner Design Science Research methodology. The proposed system model uses the Model/View/ViewModel (MVVM) architecture and is designed to integrate with supporting services, including Firebase, the Google Maps API, and the Midtrans Payment Gateway. This artifact model serves as a basis and initial recommendation for the Makassar City Government in developing a tangible, operational digital parking application that can be implemented and tested in subsequent research or policy phases. The research results indicate that the proposed digital parking system model has the potential to increase transparency and accountability in parking management and support sustainable smart city planning, particularly in Makassar.